2019
DOI: 10.7764/rdlc.17.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the occupational hazard perception of building construction workers from a psychometric paradigm and considering sociodemographic variables

Abstract: Historically, the construction industry has presented high accident rates, and in order to get a deeper understanding and making right decisions, it is interesting to consider the risks from a worker's point of view. This research addresses the perception of risks by construction workers from a psychometric paradigm and considering some sociodemographic variables. The study considered a sample consisted of a group of workers who belong to the Chilean construction industry, particularly from the building constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
(67 reference statements)
0
2
1
3
Order By: Relevance
“…These findings agree with Oah et al [ 22 ]. On the other hand, our results differ from the findings of Ellaban et al [ 41 ], Trillo-Cabello et al [ 5 ], Chaswa et al [ 42 ], and Forcael et al [ 3 ], who found that the risk perception was different depending on the age of the participants, for which they mention that this demographic variable is a factor that can influence such perceptions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings agree with Oah et al [ 22 ]. On the other hand, our results differ from the findings of Ellaban et al [ 41 ], Trillo-Cabello et al [ 5 ], Chaswa et al [ 42 ], and Forcael et al [ 3 ], who found that the risk perception was different depending on the age of the participants, for which they mention that this demographic variable is a factor that can influence such perceptions.…”
Section: Discussioncontrasting
confidence: 99%
“…According to United States data, workers in the construction industry account for about six to eight percent of all workers, and injuries and deaths are not uncommon. Although the construction industry sector has had significant technological and procedural advances, these have not always positively affected risk and accident prevention [ 3 ]. Nowadays, construction workers must shoulder a high degree of risk [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…[34] Existen tambien algunos estudios que miden la percepción del riesgo asociados a la seguridad y salud ocupacional, y que estan ligados al engagemente laboral, de los cuales se nota que hay una relación directa entre ambas variables. [39], [40], [41] El presente estudio tuvo como objetivo evaluar la mejora en la calidad del servicio analizando la relación entre los factores psicosociales establecidos por el Ministerio de Trabajo y el Engagement en el trabajo en sus tres dimensiones: vigor, dedicación y absorción, en una empresa de servicios de mantenimiento de equipos de transporte vertical en la ciudad de Guayaquil, Ecuador.…”
Section: Marco Teóricounclassified
“…Esta relação positiva entre a perceção de risco e a adoção de comportamentos seguros é evidenciada em diversos estudos em contexto laboral (Arezes e Miguel, 2008;Rundmo, 1996;Mullen, 2004;Seo, 2005;Arezes e Bizarro, 2011;Brewer et al, 2004). O paradigma psicométrico (Fischhoff et al, 1978) considera o risco como subjetivo e multidimensional e é amplamente utilizado para quantificar e caracterizar a perceção de risco (Fox-Glassman e Weber, 2016; Forcael et al, 2018). O modelo utiliza uma análise composta por nove dimensões ou atributos (A1 a A9) da perceção do risco, e permite também a avaliação quantitativa da perceção global de risco (G), sendo possível identificar quais as dimensões que mais influência exercem sobre esta (INSHT, 2001;Rodríguez-Garzón et al, 2021).…”
Section: Introductionunclassified